Recurrent activity-induced headache associated with posttraumatic dural adhesion of the middle meningeal artery: A case report. (March 2020) - Elisevich, Lee; Singer, Justin; Walsh, Meggen
Background: The middle meningeal artery is surrounded by a plexus of afferent fibers shown to be involved in the progression of some forms of headache, especially migraine. Posttraumatic headache disorders sharing characteristics with migraine and involving the middle meningeal artery are not readily available in the literature. Case description: This report describes a posttraumatic headache disorder in a middle-aged woman in which the causative factor proved to be a pathology of the left middle meningeal artery that resulted from trauma. Her pain could be triggered by moderate accelerative changes, occurring in the left frontotemporal region, and shared characteristics with migraine. Resection of a portion of the left middle meningeal artery has completely eliminated her pain syndrome. Conclusion: This case further elucidates associations between the middle meningeal artery and headache. The presentation of posttraumatic headache sharing characteristics with migraine should suggest the possibility of a middle meningeal artery abnormality.